Diagnostic accuracy of fine needle aspiration cytology in soft tissue tumors: our institutional experience - Tailor, Hemali J.; Bhagat, Vasudha M.; Kaptan, Kumar Bhargav R.; Italiya, Sonal L.; Balar, Hasmukh R.; Agarwal, Manik P. (International Journal of Research in Medical Sciences, 2017)
Background: Diagnosis of Soft tissue tumors by FNAC (Fine needle aspiration cytology) is one of the diagnostic modality of choice in pathological evaluation of soft tissue neoplasms especially to differentiate from the non-neoplastic soft tissue lesions. It is challenging and controversial. Very few centers rely on simple FNAC for diagnosis which is largely due to a lack of experience, familiarity, confidence and tricky cytological features. Methods:We have studied 140 cases of soft-tissue tumors by simple FNAC procedure done by cytopathologist from 01/01/2012 to 31/12/2012. After considering thorough history, clinical, radiology and other findings all cases were reported by the experienced faculty in cytopathology section of our institute. Results:Out of total 140 cases of soft tissue tumors 131 (93.58%) were benign and 9 (6.42%) were malignant. In benign category maximum numbers were lipoma 105 cases (80.15%) followed by benign neural tumors 5 cases (3.82%), ganglion 4 cases (3.05%), benign fibrohistiocytic lesions 2 cases (1.53%) and others. Conclusions: Current study demonstrates that FNAC is valuable as a primary tool in diagnosing soft tissue tumors specifically benign lesions like lipomatous tumors, high grade malignant sarcoma and recurrent lesions. Findings are well supported by histopathological correlation.